Abrupt warming and alpine glacial retreat through the last deglaciation in Alaska interrupted by modest Northern Hemisphere cooling - Tulenko, Joseph P.; Briner, Jason P.; Young, Nicolás E.; Schaefer, Joerg M. (Climate of the Past, 2024)
Alpine glacier-based temperature reconstructions spanning the last deglaciation provide critical constraints on local to regional climate change and have been reported from several formerly glaciated regions around the world yet remain sparse from high-northern-latitude regions. Using newly and previously 10Be-dated moraines, we report paleo-glacier equilibrium line altitudes (ELAs) for 15 time slices spanning the Last Glacial Maximum (LGM) to the Little Ice Age (LIA) for a valley in the western Alaska Range. We translate our ELA reconstructions into a proxy for summer temperature by applying a dry adiabatic lapse rate at each reconstructed ELA relative to the outermost LIA moraine. We observe ∼4 °C warming through the last deglaciation at our site that took place in two steps following initial gradual warming: ∼1.5 °C abrupt warming at 16 ka, ∼2 kyr after the onset of global CO2 rise, and ∼2 °C warming at ∼15 ka, near the start of the Bølling. Moraine deposition and modest summer cooling during Heinrich Stadial 1 and the early Younger Dryas (YD) suggest that despite these events being expressed more strongly in wintertime, the classic blueprint of North Atlantic climate variability extends to the western Arctic region.